2018
DOI: 10.1039/c8an00011e
|View full text |Cite
|
Sign up to set email alerts
|

Gas-generating reactions for point-of-care testing

Abstract: Gas generation-based measurement is an attractive alternative approach for POC (Point-of-care) testing, which relies on the amount of generated gas to detect the corresponding target concentrations. In gas generation-based POC testing, the integration of a target recognition component and a catalyzed gas-generating reaction initiated by the target introduction can lead to greatly amplified signals, which can be highly sensitive measured via distance readout or simple hand-held devices. More importantly, numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 101 publications
0
21
0
Order By: Relevance
“…Due to excellent catalysis performance and robustness at the ambient temperature for the on-site detection, various nanomaterials have been employed as catalysts in the POCTs. Compared with traditional enzyme-based catalytic reactions, nanomaterials can provide more stable and efficient catalytic properties for signal amplification, such as higher sensitivity by versatile high-surface-to-volume-ratio nanostructures, higher robustness in a complex nonlab setting, and versatile functionalization via a controllable self-assembly or surface modification. Numerous metallic and carbon-based nanomaterials , were reported as highly sensitive catalysts for colorimetric, chemiluminescent, , or electrochemical detection. For instance, Yang’s group reported that platinum nanoparticles (PtNPs) generated more than 400 times O 2 per second than common catalase, resulting in much higher detection sensitivity than catalase methods.…”
mentioning
confidence: 99%
“…Due to excellent catalysis performance and robustness at the ambient temperature for the on-site detection, various nanomaterials have been employed as catalysts in the POCTs. Compared with traditional enzyme-based catalytic reactions, nanomaterials can provide more stable and efficient catalytic properties for signal amplification, such as higher sensitivity by versatile high-surface-to-volume-ratio nanostructures, higher robustness in a complex nonlab setting, and versatile functionalization via a controllable self-assembly or surface modification. Numerous metallic and carbon-based nanomaterials , were reported as highly sensitive catalysts for colorimetric, chemiluminescent, , or electrochemical detection. For instance, Yang’s group reported that platinum nanoparticles (PtNPs) generated more than 400 times O 2 per second than common catalase, resulting in much higher detection sensitivity than catalase methods.…”
mentioning
confidence: 99%
“…The methods based on POCT can be divided into self-driving testing and external force-driving testing according to driving force [31]. Self-driving detection includes the use of capillary effect, negative pressure, or chemical reaction to generate gas [32,130], etc. to promote the reaction and output related signals, the external force-driving detection usually uses hand push, finger trigger button etc.…”
Section: Detection Methods Based On Point-of-care Testing (Poct)mentioning
confidence: 99%
“…One serial of point-of-care detection method has been developed by using different signal-amplifying nanomaterials as substitutes for horseradish peroxidase (HRP), such as the introduction of the emerging platinum nanoparticles (PtNPs) [11][12][13]. The catalytic efficiency of PtNPs has been shown to be 400 times higher than that of catalase [14]. Due to the high cost and low availability of PtNPs, monometallic catalysts are substituted by bimetallic or multimetal catalysts [15,16].…”
Section: Introductionmentioning
confidence: 99%